Kendala dan Kesiapan Lembaga Pemerintah Indonesia dalam Penerapan Akuntansi Agrikultur - Martadi, Indiana Farid (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2022)
The aim of this research is to analyze about the constrains and readiness of Indonesian government organizations in implementing the PSAP – Agriculture (Draft). This research was conducted in two agencies in the Ministry of Marine Affairs and Fisheries and two agencies in the Ministry of Agriculture. This study was using a qualitative methods by using initial questionnaire to obtain general description about accounting of biological assets and their agriculture products at the four working units as described. Advance confirmation and evidence collection was carried out remotely right after the answers of the initial questionare was received. The results of this study indicated that asset valuation is the biggest obstacle to the four agencies in implementing the PSAP - Agriculture (Draft), due to the absence of active market. Regulation about State’s Property was also a problem to those agencies in presenting biological assets according to PSAP - Agriculture (Draft). Tujuan penelitian ini adalah untuk menganalisa terhadap kendala dan kesiapan penerapan Draf PSAP – Agrikultur pada organisasi pemerintah di Indonesia. Penelitian ini dilakukan pada dua unit kerja di Kementerian Kelautan dan Perikanan serta dua unit kerja di Kementerian Pertanian. Penelitian ini menggunakan metode deskriptif kualitatif dengan menggunakan kuesioner awal untuk mendapatkan gambaran umum terkait akuntansi aset biologis produk agrikulturnya pada keempat unit kerja. Konfirmasi lanjutan dan pengumpulan bukti-bukti dilakukan secara jarak jauh setelah jawaban atas kuesioner awal diterima. Hasil penelitian ini menunjukkan bahwa, penilaian aset merupakan kendala terbesar bagi keempat unit dalam penerapan draf PSAP – Agrikultur, karena tidak adanya pasar aktif. Peraturan terkait Barang Milik Negara juga menjadi kendala bagi keempat unit kerja tersebut dalam menyajikan aset biologis sesuai draf PSAP – Agrikultur.